2019
DOI: 10.13045/jar.2019.00325
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Clinical Study on the Accuracy and Safety of Ultrasound-guided Gyeontonghyeol (BP-LE6) Acupuncture: A Prospective Randomized, Single Blinded Crossover Study

Abstract: Background: The purpose of this study was to assess the accuracy and safety of procedures using ultrasound equipment for acupuncture treatment. Methods: A pilot, prospective randomized, single blinded, crossover clinical study on the accuracy and safety of ultrasound-guided Gyeontonghyeol (BP-LE6) acupuncture treatment was conducted. Patients (n = 13) with shoulder pain were randomly divided into 2 groups. During Visit 1, ultrasound-guided BP-LE6 acupuncture was administered to the experimental group. In the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…Recent studies have suggested that using ultrasonography may be helpful for avoiding adverse event following acupuncture treatments and educational efficacy [ 19 , 20 , 21 , 22 , 23 ]. In the results of this study, it was also possible to predict the tendency of the ANIR to appear deeper when the BMI of subjects increased, but it was difficult to know whether the liver was damaged when the acupuncture needle was actually inserted.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that using ultrasonography may be helpful for avoiding adverse event following acupuncture treatments and educational efficacy [ 19 , 20 , 21 , 22 , 23 ]. In the results of this study, it was also possible to predict the tendency of the ANIR to appear deeper when the BMI of subjects increased, but it was difficult to know whether the liver was damaged when the acupuncture needle was actually inserted.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography may also be beneficial in minimizing side events during acupuncture treatments as well as educational benefits of correct needle positioning [14][15][16][17]. This study is significant in that it is the first study to analyze the needling depth and anatomical characteristics of acupoint CV23 using ultrasound.…”
Section: Menmentioning
confidence: 98%
“…맹검하에 시행하는 자침에 대해 효과성과 안전성 차이를 비교 하는 연구, 초음파 유도하 자침이 효과적이라는 증례 보고가 다수 확인되고 있다 [25][26][27]31,32,83,84) . 저자들은 향후 연구 방향을…”
Section: 현재 국내외 연구에서는 초음파 유도하에 시행하는 자침과unclassified